2013
DOI: 10.1111/apha.12083
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin relaxes rat tail main artery partly via a PKG‐mediated stimulation of KCa1.1 channels

Abstract: The natural flavonoid quercetin relaxes the rat tail main artery partly via a PKG-mediated stimulation of smooth muscle KC a 1.1 channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Similar results are described in the literature for other flavonoids that promote relaxation in rat aorta through the activation of K + channels; for example, pinocembrin activates K ATP , K Ca and K V [28], (‒)-epigallocatechin-3-gallate activates K ATP , SK Ca , IK Ca and BK Ca [29], and quercetin acts on BK Ca [30].…”
Section: Resultssupporting
confidence: 77%
“…Similar results are described in the literature for other flavonoids that promote relaxation in rat aorta through the activation of K + channels; for example, pinocembrin activates K ATP , K Ca and K V [28], (‒)-epigallocatechin-3-gallate activates K ATP , SK Ca , IK Ca and BK Ca [29], and quercetin acts on BK Ca [30].…”
Section: Resultssupporting
confidence: 77%
“…Potassium channels are determinant for the maintenance of the cellʼs normal membrane potential and the regulation of vascular tone [34,35]. Recent studies showed that quercetin activated BK Ca currents in RCA by production of H 2 O 2 [36] and relaxed the rat tail main artery partly via a protein kinase G-mediated stimulation of BK Ca 1.1 channels [37]. CA is irreplaceable in nursing cardiac cells, and K V plays an important role in regulating coronary circulation [35,38], but until now, the effects of quercetin on CA and, especially, the involvement of K V and LVGC in the effects have not been clarified yet.…”
mentioning
confidence: 99%
“…Data were collected once the current amplitude had been stabilized (usually 8-10 min after the whole-cell configuration had been obtained). K Ca 1.1 current did not run down during the following 20-30 min under the present experimental conditions [29].…”
Section: Whole-cell Patch-clamp Recordingsmentioning
confidence: 41%
“…The current-voltage relationships were calculated on the basis of the values recorded during the last 200 ms of each test pulse (leakage corrected). K Ca 1.1 current was isolated from other currents as well as corrected for leakage using 1 mM TEA, a specific blocker of K Ca 1.1 channels [29].…”
Section: Whole-cell Patch-clamp Recordingsmentioning
confidence: 99%